2021
DOI: 10.3390/ijms22062960
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of microRNA-221/2 and 17-92 Families in Primary Glioblastoma Patients Treated with Postoperative Radiotherapy

Abstract: MicroRNAs (miRs) are non-coding master regulators of transcriptome that could act as tumor suppressors (TSs) or oncogenes (oncomiRs). We aimed to systematically investigate the relevance of miRs as prognostic biomarkers in primary glioblastoma multiforme (GBM) treated with postoperative radio(chemo)therapy (PORT). For hypothesis generation, tumor miR expression by Agilent 8x15K human microRNA microarrays and survival data from 482 GBM patients of The Cancer Genome Atlas (TCGA cohort) were analyzed using Cox-PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
(44 reference statements)
1
3
0
Order By: Relevance
“…It is also significantly up-regulated in glioma tissues and positively correlates with the glioma grade (26). MiR-19b expression is associated with an unfavorable prognosis of GBM patients (27,28), a finding also confirmed in our study (Fig. 1C).…”
Section: Discussionsupporting
confidence: 90%
“…It is also significantly up-regulated in glioma tissues and positively correlates with the glioma grade (26). MiR-19b expression is associated with an unfavorable prognosis of GBM patients (27,28), a finding also confirmed in our study (Fig. 1C).…”
Section: Discussionsupporting
confidence: 90%
“…High expression of miR‐1258 , miR‐935 and miR‐128‐3p was associated with better overall survival (OS) in patients with GBM, 23 , 24 , 25 while low miR‐542‐3p and miR‐221/222 clusters expression was associated with better OS in patients with GBM. 26 , 27 Previous studies evaluated the effect of cell‐free circulating RNA on patients with GBM. Nadaradjane et al 28 found that miR‐370‐3p could be treated in patients with GBM by enhancing temozolomide sensitivity, while it could not be used as a cell‐free circulating biomarker and was not associated with patient OS.…”
Section: Microrna Smentioning
confidence: 99%
“…The average survival time of patients with glioma is 12–15 months, the 5‐year survival rate is <5%, and the survival and prognosis of patients with GBM are worse 22 ; thus, it is important to evaluate the patient's prognosis. High expression of miR‐1258 , miR‐935 and miR‐128‐3p was associated with better overall survival (OS) in patients with GBM, 23–25 while low miR‐542‐3p and miR‐221/222 clusters expression was associated with better OS in patients with GBM 26,27 . Previous studies evaluated the effect of cell‐free circulating RNA on patients with GBM.…”
Section: Micrornasmentioning
confidence: 99%
“…Targeting DNA repair mechanisms with PARP inhibitors, and mutant IDH enzyme and gene fusions with appropriate inhibitors holds potential for treating GBM patients with such genetic alterations (171,172,(174)(175)(176). Identification of several markers relevant to GBM diagnostics using liquid biopsies with NGS for circulating free DNA and/or circulating tumor cells could be used in molecular diagnosis of cytological specimens and potential administration of innovative precision therapy (177,178).…”
Section: Precision Oncology For Gliomas: Targeting Spatial Heterogeneitymentioning
confidence: 99%